Factors Affecting the Avoidance of Online Advertising on Facebook of Gen Z in Hanoi (International Journal of Scientific Research and Management (IJSRM), 2024)
Online media has become a primary platform for brands to reach consumers, but the proliferation of advertisements has led to a surge in ad avoidance behaviors, especially among Generation Z. This study examines the factors influencing Generation Z’s ad avoidance behavior on Facebook. Quantitative data from 180 Hanoi-based Gen Z respondents were collected and analyzed using SPSS, while qualitative preliminary research provided additional insights. The findings indicate that perceived goal impediment (PGI), privacy concerns (PC), negative experiences (NE), ad skepticism (AS), and ad overload (AO) significantly contribute to ad avoidance. These results offer valuable implications for online advertisers to improve the effectiveness of their campaigns and reduce ad avoidance among Gen Z consumers.